2015
DOI: 10.3390/catal5020926
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Particle Size and Operating Conditions on Pt3Co PEMFC Cathode Catalyst Durability

Abstract: Abstract:The initial performance and decay trends of polymer electrolyte membrane fuel cells (PEMFC) cathodes with Pt3Co catalysts of three mean particle sizes (4.9 nm, 8.1 nm, and 14.8 nm) with identical Pt loadings are compared. Even though the cathode based on 4.9 nm catalyst exhibited the highest initial electrochemical surface area (ECA) and mass activity, the cathode based on 8.1 nm catalyst showed better initial performance at high currents. Owing to the low mass activity of the large particles, the ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
58
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 51 publications
2
58
0
Order By: Relevance
“…Gummalla et al reported this catalyst to have a metal surface area of 35 m 2 /g-Pt, as determined by gas phase CO adsorption on the catalyst powder, an XRD-determined lattice spacing of 3.848 Å, and Pt and Co contents of 37.9 and 3.88 wt% (74.7 mol% Pt and 25.3 mol% Co), respectively, as determined by inductively-coupled plasma optical emission spectroscopy (ICP-OES). 17 A representative TEM image of the catalyst powder and the PSDs derived from TEM images are shown in Figure 1. Speder et al have shown limitations of PSD analyses based on TEM alone, based on the fact that particle sizes might be over/underestimated due to the limited contrast between the nanoparticles and the support.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gummalla et al reported this catalyst to have a metal surface area of 35 m 2 /g-Pt, as determined by gas phase CO adsorption on the catalyst powder, an XRD-determined lattice spacing of 3.848 Å, and Pt and Co contents of 37.9 and 3.88 wt% (74.7 mol% Pt and 25.3 mol% Co), respectively, as determined by inductively-coupled plasma optical emission spectroscopy (ICP-OES). 17 A representative TEM image of the catalyst powder and the PSDs derived from TEM images are shown in Figure 1. Speder et al have shown limitations of PSD analyses based on TEM alone, based on the fact that particle sizes might be over/underestimated due to the limited contrast between the nanoparticles and the support.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore any comparisons between larger annealed Pt-alloys and typical commercial Pt catalysts with smaller mean particle sizes are not straightforward. 6,17 In this work, efforts were made to investigate the durability and degradation mechanisms of similar sized Pt and Pt 3 Co electrocatalysts in the aqueous and membrane-electrode assembly (MEA) environments.Recent work has shown that anomalous small-angle X-ray scattering (ASAXS) is an effective technique for observing in-situ and inoperando evolutions of Pt catalyst PSDs leading to insights into their degradation mechanism(s).14,18-22 A comprehensive discussion of the * Electrochemical Society Student Member. z E-mail: dmyers@anl.gov ASAXS method and its use in characterizing carbon-supported metal catalysts can be found in several publications and textbooks.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These alloy catalysts have much higher mass activity for ORR than Pt/C catalysts, and, due to their larger particle size (4-5 nm), can be more stable than the 2-3 nm Pt/C traditionally used to obtain high ORR mass activities. 4 However, Co, with a standard dissolution potential of −0.28V vs. NHE 24 is unstable at typical PEFC cathode potentials (∼0.6 to ∼0.9 V). One objective of this work is to provide initial quantitative data on the dissolution behavior of Co in commercial PtCo/C catalysts as a function of potential and potential profile.…”
mentioning
confidence: 99%
“…Whereas only in-cell studies can properly characterize the performance and stability of advanced polymer electrolyte fuel cell (PEFC) oxygen reduction reaction (ORR) catalysts, [1][2][3][4] the fuel cell environment presents challenges to the real-time measurement of the catalyst degradation processes. Therefore, the bulk of our understanding of Pt and transition metal dissolution from Pt and Pt alloy catalysts, including real-time resolution of the dissolution processes during potential cycling, has been obtained through aqueous studies.…”
mentioning
confidence: 99%